Completeness of reporting of randomised controlled trials including people with transient ischaemic attack or stroke: A systematic review - Wilson, B; Burnett, P; Moher, D; Altman, D; Salman, R (SAGE Publications, 2018)
Objective: To assess the adherence of stroke randomised controlled trials (RCTs) to CONSORT reporting guidelines, and investigate the factors that are associated with completeness of reporting. Design: Two reviewers assessed the published report of the final primary results of stroke RCTs with a 10-point truncated CONSORT reporting checklist, to investigate adherence over time, univariable associations, and independent associations with total CONSORT reporting score in a multiple linear regression model. Data sources: Random sample of stroke RCTs from the Cochrane Stroke Group’s Trial Register. Eligibility criteria: Primary published report of the final results of transient ischaemic attack (TIA) or stroke RCTs, published in English in 1997-2016 inclusive. Results: In this random sample of 177 stroke RCTs, the mean score on the truncated CONSORT checklist was 5.8 (SD 2.2); reporting improved from 1997-2000 (4.9 SD 2.0) to 2001-2009 (5.8 SD 2.1) and to 2010-2016 (6.8 SD 2.1). A higher CONSORT score was independently associated with publication during epochs following a revision of CONSORT reporting guidelines (p<0.001), journal endorsement of the CONSORT reporting guideline at the time of RCT publication (p<0.001), and modified journal impact factor using median citation distribution (p=0.012). Conclusions: Stroke RCT reporting to CONSORT standards has improved over time, but could be better. Journal endorsement and enforcement of CONSORT reporting guidelines could further improve the reporting of stroke RCTs.